PRESIDENTIAL APPROVAL AND VOTE FOR THE RULING PARTY IN COSTA RICA (1982-2022). COMPARATIVE ANALYSIS OF THE EXCEPTIONS - Díaz Rodríguez, Orestes Enrique (2023)
The approval of the current president has been a reasonably reliable predictor of the success or defeat of the ruling party in Costa Rica. To verify this, we formed a sample that covered the presidential elections held between 1982 and 2022. The results suggest that the Costa Rican voter tends to reward or punish the official presidential candidate depending on the perception they have of the performance of the current president. The 1990 and 1994 elections were exceptions to this dynamic. Both experiences are analyzed in the light of comparative experience.